Pragmatic Analysis of Humor in American Animated Sitcom “American Dad! Season 17” - Dahlan, Dahlan (Journal of Islamic Culture and Literature (JICeL), 2023)
This research examines the flouting and breaking of maxims by the characters in the sitcom American Dad! Season 17 it employs the Grice cooperative principle theory as well as Attardo’s function of humor. This research used qualitative research method. The source of data is American animated sitcom American Dad! Season17. The research reveals two findings. The first is that all the four types of flouting are employed by the characters to create humor in American Dad! season17. They are flouting maxim of quantity, flouting maxim of quality, flouting maxim of relation, and flouting maxim of manner. Flouting maxim of relation is mostly employed by the characters to create humor, all the functions of Humor are found in the sitcom; they are social management, decommitment, mediation, and defunctionalization. For breaking maxim, only two functions are found in the sitcom; they are social management, and defunctionalization.